High‐Throughput Approaches in Carbohydrate‐Active Enzymology: Glycosidase and Glycosyl Transferase Inhibitors, Evolution, and Discovery. Issue 37 (17th July 2019) - Chao, Lemeng; Jongkees, Seino
Abstract: Carbohydrates are attached and removed in living systems through the action of carbohydrate‐active enzymes such as glycosyl transferases and glycoside hydrolases. The molecules resulting from these enzymes have many important roles in organisms, such as cellular communication, structural support, and energy metabolism. In general, each carbohydrate transformation requires a separate catalyst, and so these enzyme families are extremely diverse. To make this diversity manageable, high‐throughput approaches look at many enzymes at once. Similarly, high‐throughput approaches can be a powerful way of finding inhibitors that can be used to tune the reactivity of these enzymes, either in an industrial, a laboratory, or a medicinal setting. In this review, we provide an overview of how these enzymes and inhibitors can be sought using techniques such as high‐throughput natural product and combinatorial library screening, phage and mRNA display of (glyco)peptides, fluorescence‐activated cell sorting, and metagenomics. Abstract : Enzyme discovery : High‐throughput approaches are a powerful tool for pushing enzymology in new directions. Particularly carbohydrate‐active enzymes, with their high diversity and many subtleties in substrate scope, can benefit from new developments in this field. This minireview focuses on innovative approaches to the discovery of new inhibition types, the tuning of enzyme reactivity, and the search for new enzymes.